Crystal structure of 3-(2-hydroxyphenyl)-1-(2’-hydroxyphenyl)-2-propen-1-one, C15H12O3 - M-C, Feng; G-Y, Yeap; M-G, Tay; S-G, Teoh; RA, Howie; H, Rufino (Degruyter Publisher, 1999)
C15H12O3, monoclinic, C12/cl (No. 15), a = 23.63(4) Â, b = 5.58(1) Â, c = 17.98(3) Â, β = 95.1(1)°, V = 2361 Â3, Z= 8, Rgl(F) = 0.108, Rv/(F2) = 0.204, T= 298 K.